2011
DOI: 10.5012/bkcs.2011.32.12.4392
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Metal-Semiconductor Interface in Porous Silicon and Its Photoelectrochemical Hydrogen Production

Abstract: Porous silicon with a complex network of nanopores is utilized for photoelectrochemical energy conversion. A novel electroless Pt deposition onto porous silicon is investigated in the context of photoelectrochemical hydrogen generation. The electroless Pt deposition is shown to improve the characteristics of the PS photoelectrode toward photoelectrochemical H + reduction, though excessive Pt deposition leads to decrease of photocurrent. Furthermore, it is found that a thin layer (< 10 µm) of porous silicon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…13 Recently, Oh et al, investigated the photocurrent efficiency of pSi and found that platinum (Pt) impregnation by electroless deposition reduced the overpotential for photoelectrochemical hydrogen generation. 14 More recently, Ott et al, 15 fabricated a p-type silicon/molecular electro-catalyst junction using a dithiolatebridged [FeFe] motif, a derivative of the Fe 2 S 2 (CO) 6 hydrogenase analogue used in our earlier work. 2 In this study, we aimed to increase the efficiency of the solar-driven hydrogen generation by harnessing the properties of pSi in combination with [FeFe] hydrogenase analogues as electrocatalysts.…”
mentioning
confidence: 99%
“…13 Recently, Oh et al, investigated the photocurrent efficiency of pSi and found that platinum (Pt) impregnation by electroless deposition reduced the overpotential for photoelectrochemical hydrogen generation. 14 More recently, Ott et al, 15 fabricated a p-type silicon/molecular electro-catalyst junction using a dithiolatebridged [FeFe] motif, a derivative of the Fe 2 S 2 (CO) 6 hydrogenase analogue used in our earlier work. 2 In this study, we aimed to increase the efficiency of the solar-driven hydrogen generation by harnessing the properties of pSi in combination with [FeFe] hydrogenase analogues as electrocatalysts.…”
mentioning
confidence: 99%
“…Distinct from the previously reported silicon nanostructures prepared in a similar way (i.e. MACE), [12][13][14][15][16][17][18][19] we nd that the Si NBs we obtained are tilted with respect to the normal of the Si substrate at an angle of 60 -70 possibly due to the unique etching process in which the gold catalyst lm with a mesh size of micrometers was employed. When used for solar HER, the tilted Si NB arrays exhibit markedly enhanced photocurrent density as well as improved photovoltage and charge transfer kinetics, compared with the planar p-Si and Si NW arrays reported previously.…”
mentioning
confidence: 58%
“…Results of the photoelectrochemical performance achieved with PECs utilizing RGO-based photocathodes are reported in Table 4. Finally, we report now on the photoelectrocatalytic activity of p-Si based photocathodes for HER when silicon has different morphologies (nanowires, micropyramidal, nanomesh), various degree of doping (p-, n + and n + pp + ), and diverse types of photoelectrocatalyst (metallic, p-type semiconducting, metal alloy) [63,97,99,111,[125][126][127][128][129][130][131][132][133][134][135][136][137]. A scheme of the energy levels involved in the interface p-Si/electrolyte for HER is given in Figure 19 [126].…”
Section: Photoelectrodes Of P-type For Non Fossil Fuel (H 2 ) Productionmentioning
confidence: 99%